The Politics of Symbols and the Symbolization of 9/11 (American Journal of Islam and Society, 2004)
The responses to 9/11 are conferring symbolic meaning on the facts of 9/11. The transformation follows the general pattern of symbolic politics. In the process, Islam is implicated, by default, through three interconnected issues that are driving the discourse of 9/11: global security, the imperatives of modernity, and the reassessment of Islam. Islam is symbolized either in terms of a politics of confrontation or of cooptation. What is left out is the self-understanding of Islam. Contrary to the conventional opinion that Islam as a religion is not at issue, the very meaning of Islam is at stake in the politics of symbols.